Intra‐bone bone marrow transplantation from hCD47 transgenic pigs to baboons prolongs chimerism to >60 days and promotes increased porcine lung transplant survival. (23rd September 2019) - Watanabe, Hironosuke; Ariyoshi, Yuichi; Pomposelli, Thomas; Takeuchi, Kazuhiro; Ekanayake‐Alper, Dilrukshi K.; Boyd, Lennan K.; Arn, Scott J.; Sahara, Hisashi; Shimizu, Akira; Ayares, David; Lorber, Marc I.; Sykes, Megan; et al.
Abstract: Background: We have recently demonstrated that human‐CD47 (hCD47) expressed on endothelial cells of porcine lung xenografts extended median graft survival from 3.5 days to 8.7 days in baboons. Intra‐bone bone marrow transplantation (IBBMTx) in a pig‐to‐baboon model was previously shown to markedly prolong the duration of macrochimerism up to 21 days from 1 to 4 days by intravenous BMTx. We now examined whether the use of hCD47 transgenic (Tg) BM further prolonged the duration of chimerism following IBBMTx. We then tested if lung xenograft survival was prolonged following IBBMTx. Methods: Baboons received GalTKO‐hCD47/hCD55Tg (n = 5) or ‐hCD55Tg (n = 1) or ‐hCD46/HLA‐E Tg (n = 1) pig IBBMTx. Macrochimerism, anti‐pig T cells and antibody responses were assessed. Animals received lung xenografts from either hCD47+ or hCD47‐ porcine lungs 1‐3 months later. Results: All baboons that received hCD47Tg porcine IBBM maintained durable macrochimerism >30 days, and two maintained chimerism for >8 weeks. Notably, anti‐pig antibody levels decreased over time and anti‐pig cellular unresponsiveness developed following IBBMTx. Lungs from hCD47Tg IBBMTx matched pigs were transplanted at day 33 or day 49 after IBBMTx. These animals showed extended survival up to 13 and 14 days, while animals that received lungs from hCD47 negative pigs displayed no prolonged survival (1‐4 days). Conclusion: This is the first report demonstrating durable macrochimerism beyond 8 weeks, as well as evidence for B cell tolerance in large animal xenotransplantation. Using hCD47Tg pigs as both IBBMTx and lung donors prolongs lung xenograft survival. However, additional strategies are required to control the acute loss of lung xenografts.